2011
DOI: 10.1016/j.ijsu.2011.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical model to predict risk for lymphoedema after treatment of cutaneous melanoma

Abstract: This study identified a melanoma thickness >4mm, graft reconstruction, ilioinguinal lymphadenectomy and infection as risk factors for lymphoedema. From these factors, we constructed a mathematical model that successfully predicted risk of post-lymphadenectomy lymphoedema. The combined presence of these risk factors increased the chance of developing lymphoedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Indeed, some patients require lifelong suppressive antibiotic therapy and develop infections despite these treatments. Often, infections lead to increasing severity of lymphedema, suggesting that infections can injure the lymphatic system [66]. In some patients, infections are cited as a cause of secondary lymphedema, suggesting a direct role of bacteria in generating lymphatic dysfunction [67,68].…”
Section: Lymphedema Is Associated With Recurrent Infectionsmentioning
confidence: 99%
“…Indeed, some patients require lifelong suppressive antibiotic therapy and develop infections despite these treatments. Often, infections lead to increasing severity of lymphedema, suggesting that infections can injure the lymphatic system [66]. In some patients, infections are cited as a cause of secondary lymphedema, suggesting a direct role of bacteria in generating lymphatic dysfunction [67,68].…”
Section: Lymphedema Is Associated With Recurrent Infectionsmentioning
confidence: 99%
“…However, there is clinical evidence that compression wrap devices improve the quality of life and independence of patients. 12 Although infection is a significant risk factor for lymphedema, 13 patients in this study reported low rates of postoperative infection and erysipelas, probably due to the small sample size. Radiation therapy is also a risk factor, as it promotes the formation of tissue fibrosis, with consequent lymphatic vasoconstriction, significant damage to the lymph node filtration function and altered immune response.…”
mentioning
confidence: 67%
“…Other risk factors for lymphedema are melanoma thickness >4 mm, infection and graft reconstruction, and a combination of these risk factors increases the chances of developing this chronic condition. 1 Lymphedema can be diagnosed using several different objective methods, including manual perimetry (MP), water displacement, tonometry, optoelectronic volumetry and bioimpedance. 2 However many studies have diagnosed lymphedema subjectively on the basis of patients' responses to questions about their symptoms, such as heaviness and/or swelling in the limb.…”
Section: Introductionmentioning
confidence: 99%